COMPARISON OF THE EFFECTS OF NIGELLA SATIVA OIL AND LASER ON TREATMENTS ON EXPERIMENTAL WOUND HEALING IN RATS - RABAB HAJWAL AL-ZAMILY; SHROQ MOHAMED ABAS AL-TEMIMI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective:The study investigated the influences of treatment with Nigella sativa oil and laser therapy on wound healing in rats. The period of the inflammatory phase reduced through both laser and N. sativa oil actions; though, the laser was more effective than N. sativa oil, with more significant results. Methods: We used 52 healthy rats male and divided the rats randomly into three groups. The treatment protocols used included N. sativa oil in the first group, laser in the second group, and control in the third group. In all groups, we performed histopathologic evaluations on the 1st, 3rd, 5th, and 7th days after surgery. Results: The proliferation phase of each treatment indicated an increase in the number of fibroblasts, as well as stimulation of collagen formation and synthesis.Positive results on the inflammatory, proliferation, and maturation phases for both treatments of wound healing. Conclusion:Laser treatment was more effective than N. sativa oil in the first two phases of wound healing.